El inexorable resfriado del sistema judicial Colombiano (2021)
This research project, studies a topic of fundamental importance in relation to the law led to praxis. Judicial backwardness is a phenomenon that actually impedes optimal access to the administration of justice and effective execution of the public function. This research project is an attempt to analyze theproblem and its possible causes. Moreover, it is an approximation, to the conclusion that the judicial backwardness and other problems facing the jurisdictional system are not produced only by public officials and that the law actually led into practice does not only involve lawyers and scholars in this science. Law interacts directly with the population in general, regardless of their profession or trade. It is necessary to remember that the law and its applicability have a general nature, without any distinction, at least in theory.